Competencia comunicativa y análisis crítico del discurso - Rodríguez Núñez, Luz Helena (Enunciación, 2004)
The article makes a critical review of the literature that exists surrounding the topic of communicative competence and the critical analysis of the discourse. The purpose of the text is to present the need and basis or foundations of this approach of analysis of language as a tool that the language arts teacher shall include in the educational practices that are geared towards the whole development of the communicative competence, provided that he or she is faced with the challenge of educating a generation that is characterized by the discursive power of the information, of the mass media and of a globalized world.